Enhancement on SBR treatment for oily wastewater by three strains of highly efficient petroleum-degrading bacteria - LI Qian; CHEN Jixiang; YANG Xuan; PENG Cheng; WANG Tianfeng (Gongye shui chuli)
This paper investigated the effect of three efficient petroleum-degrading bacterial strains on oily wastewater treatment by sequencing batch reactor activated sludge process (SBR). The results showed that the average removal rates of COD were 90.8%, 92.8%, and 98.2%, respectively, the average removal rates of oily substance were 79.1%, 80.0%, and 92.8%, respectively, the average removal rates of NH4+-N were 87.5%, 91.4%, and 94.7%, respectively, and the average removal rates of TP were 23.8%, 30.9% and 44.4%, respectively, in the SBR with the addition of bacterial strains Ochrobactrum sp. FP1, Pseudomonas sp. X1 and Rhodococcus erythropolis KB1. Compared with the unspiked petroleum-degrading bacteria, the spiked petroleum-degrading bacterial strains could significantly improve the removal efficiency of SBR for each pollutant in the oily wastewater. Meanwhile, the system operation was stable and the shock load resistance was high. The experimental results also showed that the addition of FeCl3 to the SBR could improve the removal of TP by using chemical phosphorus removal to assist biological phosphorus removal, and improve the flocculation and sedimentation performance of activated sludge and increase the active biomass in the system. This study provided a reference for the process design and equipment operation of bio-enhanced SBR for the treatment of oily wastewater. The petroleum-degrading bacteria-enhanced SBR technology is expected to be applied to the biological treatment of oily wastewater.